High and low corruption: children, capabilities, and crime - Adams, Harry (Lexington Books, 2023)
"This book analyzes "high corruption" in terms of political corruption and high-end white-collar crime and "low corruption" in terms of juvenile delinquency and street crime. It shows how this former type of corruption contributes to the latter type and also explains how both types should be curbed"-- Provided by publisher